2016
DOI: 10.1002/anie.201511767
|View full text |Cite
|
Sign up to set email alerts
|

A Tissue‐Penetrating Double Network Restores the Mechanical Properties of Degenerated Articular Cartilage

Abstract: Incorporation of an interpenetrating polymer network into an existing single polymer network enables augmentation of the original substrate’s mechanical properties, and translation of this concept from purely synthetic materials to natural-synthetic hybrid systems provides the opportunity to reinforce mechanical properties of bulk biological substrates. In many disease states, bodily tissues experience a deterioration of mechanical properties which renders them prone to further material failure. Herein, a tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 53 publications
1
31
0
Order By: Relevance
“…The differences in COF became statistically significant between 60 w/v% treated and non-treated tissue approximately half-way into the three-hour test (24% reduction in COF compared to non-treated tissue at the test’s completion), whereas the difference in COF between 20 w/v% and non-treated tissue demonstrated a non-statistically significant (p = 0.48) 5% reduction in COF compared to non-treated tissue. The IPN dose-dependence of the frictional response agrees with the observed dose-dependence of the compressive stiffness and wear-resistance as reported in our prior study, 36 and the IPN’s reduction of friction reported herein may be one of the primary reasons causing its improvement in wear-resistance. While the magnitude of COF is affected by the presence of IPN, the characteristic shapes of the three COF curves as a function of time are not statistically significant; all three curves possess similar COF equilibration time constants.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The differences in COF became statistically significant between 60 w/v% treated and non-treated tissue approximately half-way into the three-hour test (24% reduction in COF compared to non-treated tissue at the test’s completion), whereas the difference in COF between 20 w/v% and non-treated tissue demonstrated a non-statistically significant (p = 0.48) 5% reduction in COF compared to non-treated tissue. The IPN dose-dependence of the frictional response agrees with the observed dose-dependence of the compressive stiffness and wear-resistance as reported in our prior study, 36 and the IPN’s reduction of friction reported herein may be one of the primary reasons causing its improvement in wear-resistance. While the magnitude of COF is affected by the presence of IPN, the characteristic shapes of the three COF curves as a function of time are not statistically significant; all three curves possess similar COF equilibration time constants.…”
Section: Discussionsupporting
confidence: 91%
“…This attenuation of creep deformation (22% reduction by the test’s equilibrium) is related to the increased equilibrium stiffness that the IPN imparts. 36 Similar to the COF vs time profiles, the creep deformation time profiles do not statistically significantly differ in equilibration time constant τ ε (p = 0.33), with τ ε lengthened by 9% for the 60 w/v% treated compared to non-treated tissue. This increased time constant represents the increased time required for tissue to deform in response to the constant load applied, and likely originates from two underlying mechanisms.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…A comparison of E mod values of gels with literature is presented in Table S3 (ESI †). 3,13,14,[62][63][64] To investigate the fatigue resistance of EG gels and hydrogels, consecutive cyclic compression tests were performed. Standard force was recorded against true strain, which is the absolute change in plate distance, with an elongation of 50%.…”
Section: Samplementioning
confidence: 99%
“…At the same time, addition of the reinforcing agent increases the crosslinking density resulting in stronger interactions. Common approaches for improvement of hydrogels mechanical properties utilize double network systems, [12][13][14] nanofibers, 15 tetra armed-PEG crosslinked systems, 16,17 3D printing, 18 slide-ring gels, 19,20 and introduction of charged supports. 11,21,22 Double network systems are one of the first examples of reinforced hydrogels that consist of a tightly crosslinked first network and a loosely crosslinked secondary network.…”
Section: Introductionmentioning
confidence: 99%